2010
DOI: 10.1007/s00429-010-0271-z
|View full text |Cite
|
Sign up to set email alerts
|

Histochemical visualization and diffusion MRI at 7 Tesla in the TgCRND8 transgenic model of Alzheimer’s disease

Abstract: Alzheimer's disease (AD) is a progressive neurodegenerative disorder that has been characterized by gross cortical atrophy, cellular neurodegeneration, reactive gliosis, and the presence of microscopic extracellular amyloid plaques and intracellular neurofibrillary tangles. Earlier diagnoses of AD would be in the best interest of managing the patient and would allow for earlier therapeutic intervention. By measuring the apparent diffusion coefficient (ADC) using diffusion-weighted imaging (DWI), a type of magn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 33 publications
3
15
0
Order By: Relevance
“…A trend towards higher ADC values is observed in whole brain as well as hippocampus or cortex of the A␤PP/PS1, compared to control mice, but these trends are not statistically significant. Similar findings were reported in other AD mouse model that expresses a double mutant form of hA␤PP 695 (K670 N/M671 L and V717F) [54].…”
Section: Discussionsupporting
confidence: 90%
“…A trend towards higher ADC values is observed in whole brain as well as hippocampus or cortex of the A␤PP/PS1, compared to control mice, but these trends are not statistically significant. Similar findings were reported in other AD mouse model that expresses a double mutant form of hA␤PP 695 (K670 N/M671 L and V717F) [54].…”
Section: Discussionsupporting
confidence: 90%
“…Consistent with this interpretation is the finding of a the lack of DTI differences in the slice containing the entorhinal cortex, in which immunoreactivity for pathological tau was particularly intense in the subiculum, as previously reported [29,44,45]. Using diffusion weighted imaging, however, TgCRND8 mice failed to show altered diffusivity in gray matter regions, including the hippocampus and cerebral cortex [24], regions with robust plaque deposition in the absence of neurofibrillary tangles, suggesting it is the co-occurrence of both A␤ plaques and neurofibrillary tangles that contributes to the altered DTI measures in the present study. One must exercise caution in interpreting results of DTI because changes in DTI metrics reflect differences in the diffusion behavior of water and thus imply some sort of neuropathology.…”
Section: Discussionsupporting
confidence: 83%
“…In gray matter, the trace of the diffusion tensor was decreased in both hippocampal and cortical tissue [23]. In contrast, in TgCRND8 mice, also characterized by robust A␤ plaque deposition, no differences in diffusivity were detected in hippocampal or cortical tissue using diffusion weighted imaging [24]. Studies of double transgenic APP/PSI mice [25,26], in which both A␤ plaque deposition and neuron loss occur, report elevated diffusivity measures in multiple brain regions, including gray matter-rich hippocampus and cortex.…”
Section: Introductionmentioning
confidence: 90%
“…Mueggler et al (2004) found reduced diffusivity in neocortex of APP23 transgenic mice that was accompanied by fibrillar amyloid deposits and associated gliosis, suggesting that extracellular deposition of fibrillar amyloid and/or associated glial proliferation restrict diffusion. Still, the contribution of Aβ plaques to diffusional changes remains controversial (Thiessen et al, 2010). To investigate this theory in the present study, nonparametric correlations were performed on the PiB signal and MD value from the region with significant differences in MD.…”
Section: Discussionmentioning
confidence: 99%